Peningkatan Kesadaran Masyarakat tentang Pencegahan Diabetes melalui Penyuluhan Kesehatan dan Pemeriksaan Kadar Gula Darah di Kelurahan Gadingrejo - Sutrisno Sutrisno; Andhika Rifki Perdana; Ardha Pangestu; Nabila Nabila; Astin Parastika; Lulu Anggraini; Nurzaytun Nurzaytun; Refi Fresiliya Anggraini; Rian Septa Putra; Ripki Vernando; Riza Ayu Tianda; Rima Arianti; Siti Badiur Rofiah; Utari Fatmawati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This community service program aimed to improve public knowledge and awareness regarding diabetes prevention through health education and free blood glucose screening. The activity was conducted in Gadingrejo Village, Pringsewu Regency, involving 30 participants aged 45–65 years who were identified as a high-risk group for diabetes mellitus. The intervention consisted of structured health education, dissemination of educational leaflets, and direct blood glucose, blood pressure, and uric acid measurements performed by nursing students and supervised by a lecturer. The results showed that 60% of participants had normal blood glucose levels, 26% had slightly elevated glucose levels, and 14% had high glucose levels indicating potential diabetes. Participants demonstrated strong enthusiasm, actively engaged during discussion sessions, and expressed improved understanding regarding healthy diet management, physical activity, and routine health monitoring. A short session of simple aerobic exercise was also conducted to promote regular physical activity as an easy preventive measure. Overall, this program successfully increased public awareness and early detection of diabetes risk. Strengthening local cadres’ capacity and conducting regular community-based health screening are recommended to ensure sustainable diabetes prevention efforts.